Inggris - Mirza Junianto; Sugianto Sugianto; Hairul Basri (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze changes in land cover and mangrove crown density in Langsa Barat District for the period 2000-2020. The method used in this study is the maximum likelihood classification (MLC) to determine changes in mangrove land cover while determining mangrove density using the NDVI equation. Based on the results of the analysis of changes in mangrove land cover there was an increase and decrease in area. In 2000 the area of ​​mangrove land was 1,039.17 ha, then increased in area in 2005 amounted to 1.325,59 ha (27.56%).  In 2010, the mangrove area decreased by 1.145,22 ha (15.75%).  In 2015, the mangrove area increased to 1,357.10 ha (18.50%), and finally, in 2020 there was an increase in the mangrove area to 2.027.05 ha (49.37%). While the analysis of mangrove crown density using NDVI value from 2000 to 2020, the highest crown density value was in 2020 with the category of the dense crown density of 1,509.40 ha (74.46%), while the medium crown density value was recorded in 2020 namely 517.49 ha (25.53%). Meanwhile, the lowest sparse category canopy density value was recorded in 2020 with an area of ​​0.17 ha (0.01%).